2021
DOI: 10.1093/femsec/fiab131
|View full text |Cite
|
Sign up to set email alerts
|

Apple endophyte community in relation to location, scion and rootstock genotypes and susceptibility to European canker

Abstract: European apple canker, caused by Neonectria ditissima, is a severe disease of apple. Achieving effective control is difficult with the currently available pesticides. Specific apple endophytes associated with cultivars may partially contribute to the cultivar response to the pathogen and thus could be used for disease management. We sought to determine whether the overall endophyte community differed among cultivars differing in their susceptibility to N. ditissima and to identify specific microbial groups ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 92 publications
3
22
1
Order By: Relevance
“…Liu et al (2020) and our study proved that the site was the main driver shaping the endophytic community in apple, but not the region [12]. Leone Olivieri et al (2021) studied and found that the apple endophyte community in relation to location, and scion and rootstock genotypes was susceptible to European canker [40]. Liu Jia et al (2018) stated that the mechanism by which an apple genotype, either rootstock or scion, has a determinant effect on the composition of a microbial community is not known [41].…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Liu et al (2020) and our study proved that the site was the main driver shaping the endophytic community in apple, but not the region [12]. Leone Olivieri et al (2021) studied and found that the apple endophyte community in relation to location, and scion and rootstock genotypes was susceptible to European canker [40]. Liu Jia et al (2018) stated that the mechanism by which an apple genotype, either rootstock or scion, has a determinant effect on the composition of a microbial community is not known [41].…”
Section: Discussionmentioning
confidence: 45%
“…In China, Li et al (2020) isolated and identified four strains of B. subtilis, two strains of B. velezensis, and one strain of B. amyloliquefaciens from a wild apple (Malus sieversii) [39]. Therefore, it is suggested that differences in the distribution of endophytic bacteria communities in apple leaves may depend upon the external environmental conditions, or upon different cultivation methods such as the use of pesticides [12,40,41]. Liu et al (2020) and our study proved that the site was the main driver shaping the endophytic community in apple, but not the region [12].…”
Section: Discussionmentioning
confidence: 99%
“…Further, scab disease management had an effect on the abundance of some taxa depending on bark age, orchard location, and sampling time ( Arrigoni et al, 2020 ). Interestingly, Olivieri et al (2021) mentioned the presence of significant differences between canker-resistant and susceptible apple cultivars with respect to the endophyte community.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the endophytic fungal communities of apple (e.g., Camatti-Sartori et al, 2005;Alijani et al, 2016a;Liu et al, 2017;Muresan, 2017;Afandhi et al, 2018;Liu et al, 2018;Arrigoni et al, 2020;Olivieri et al, 2021), some of which have focused on the biological control potential of the endophytes against apple fungal diseases. Alijani et al (2016a) purified about 350 isolates from the shoots, leaves, and barks of endemic and commercial apple trees in West Azerbaijan province, Iran and identified 24 species belonging to 10 genera of Ascomycota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation